The Formation of the Crimean Tatar Literary Language Based on the Urban Koine of Bakhchisaray in the seventeenth and eighteenth century - Rustemov O.D,; Stepanov E.N. (Золотоордынское обозрение)
The purpose of this work is to determine the role of the koine of the Bakhchisaray’s capital and its environs in the formation of the supra-dialect koine and the literary (standard) Crimean Tatar language in the seventeenth and eighteenth centuries. The period that we are considering in this article is quite indicative precisely in terms of the development of the Crimean Tatar literary language and its oral form – the supra-dialect koine. This time was the last stage of the fully functioning Crimean language before the Crimean Khanate lost its independence totally (1783). Phonological, lexical and grammatical norms which determined the vector of further development of the literary language of the Crimean Tatars, based mainly on the Bakhchisaray urban koine, had already crystallized in that epoch’s language. The material of this study consists of legal documents. They provide the best way to trace the processes of the formation of norms in the general Crimean supra-dialect koine, which based on the capital’s koine. Of particular value are the records of Sharia courts of the Crimean kadiys, on the one hand, and the khan’s yarliks along with letters, on the other. Both types of documents demonstrate two literary styles that were forming by different Turkic linguo-cultural traditions: that of the Golden Horde and the Crimean proper, the latter being a regional one which was influenced by the Ottoman language. The fact of lingual archaism and the mixing the phonetic, lexical and grammatical traditions of different Turkic languages in the texts of the manuscripts of official and business writing testify to the mixed character of norms in the Bakhchisaray, pre-dialect koine norms, and the norms of the literary language on the basis of the interaction of homogeneous Turkic idioms (Cumanian and Seljukian) with a small share of heterogeneous, mostly lexical, borrowings.